2009
DOI: 10.1002/mds.22484
|View full text |Cite
|
Sign up to set email alerts
|

A follow‐up study on 6‐[18F]fluoro‐L‐dopa uptake in early Parkinson's disease shows nonlinear progression in the putamen

Abstract: Sixteen subjects with de novo Parkinson's disease (PD) underwent three 6-[18F]fluoro-L-dopa (Fdopa) positron emission tomography (PET) scans during a follow-up time of 5 years (mean +/- SD 5.5 +/- 0.4 years) to study the progression of striatal dopaminergic hypofunction. Throughout the study, the smallest Fdopa uptake values were found in the dorso-caudal part of the putamen contralateral to the side with dominant motor symptoms. The rate of decline in Fdopa uptake in the contralateral putamen was faster in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
48
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 24 publications
13
48
1
1
Order By: Relevance
“…60 Autopsy studies in PD have shown a 45 % decrease in nigral cell counts during the first 10 years of PD, 10 times greater than the loss associated with normal aging, with a tendency to approach the normal age-related linear decline in the later stages. 5 53), but that at the same age of onset, the calculated preclinical durations are shorter when other tracers are used (13 years for DAT binding; six years for FD uptake, in keeping with other literature). 60 The sensitivity of imaging to detect preclinical dopaminergic dysfunction has been demonstrated in a number of high-risk groups, including asymptomatic individuals exposed to MPTP 63 and unaffected twins whose identical co-twins are affected.…”
Section: Assessment Of Disease Progression With Positron Emission Tomsupporting
confidence: 49%
“…60 Autopsy studies in PD have shown a 45 % decrease in nigral cell counts during the first 10 years of PD, 10 times greater than the loss associated with normal aging, with a tendency to approach the normal age-related linear decline in the later stages. 5 53), but that at the same age of onset, the calculated preclinical durations are shorter when other tracers are used (13 years for DAT binding; six years for FD uptake, in keeping with other literature). 60 The sensitivity of imaging to detect preclinical dopaminergic dysfunction has been demonstrated in a number of high-risk groups, including asymptomatic individuals exposed to MPTP 63 and unaffected twins whose identical co-twins are affected.…”
Section: Assessment Of Disease Progression With Positron Emission Tomsupporting
confidence: 49%
“…While the duration and severity of motor function, the corresponding decrease of dopamine, tyrosine hydroxylase (TH), dopamine transporter (DAT), and vesicular monoamine transporter-2 (VMAT-2) immunoreactivity in striatum are negatively correlated with total SN aSyn burden and neuronal loss [7,22,33,86], the latter shows no correlation with LB formation [54], and no relationship between LB stage and both clinical severity of PD (Hoehn and Yahr score) and age at death were found [15]. Progression of putaminal DAergic hypofunction (L-dopa uptake) shows a nonlinear pattern at least on the contralateral side being faster in early PD [13]. The proportion of LB-bearing SN cells appears to be stable over time, involving 3.6% of neurons in average, suggesting that, during the course of disease, the destruction of LBs may be equal to their production and that they are destroyed together with the afflicted neurons.…”
Section: Formation Of Lewy Bodiesmentioning
confidence: 92%
“…Specifically, positron emission tomography (PET) using 6-[ 18 F]-fluoro-3,4-dihydroxy-l-phenylalanine ([ 18 F]-F-DOPA), [ 11 C]-2␤-carbomethoxy-3␤-(4-fluorophenyl)-tropane ([ 11 C]-CFT), and [ 11 C]-raclopride has been clinically used to evaluate DA synthesis capacity, DA transporter (DAT), and DA receptors, respectively. Several PET studies in humans (Bruck et al, 2009;Nurmi et al, 2003;Rinne et al, 2001) and monkeys (Oiwa et al, 2003;Wullner et al, 1994) have demonstrated a behavior-related decrease in DA 0165-0270/$ -see front matter © 2010 Elsevier B.V. All rights reserved. doi:10.1016/j.jneumeth.2010.05.009 synthesis or DAT density in the striatum.…”
Section: Introductionmentioning
confidence: 98%